Association between the oxidative balance score and low muscle mass in middle-aged US adults - Chen, Kun; Yin, Qiang; Guan, Jiangan; Yang, Jingwen; Ma, Yuan; Hu, Yu; Chen, Chan; Chen, Wenwen (Frontiers in Nutrition, 2024)
Background: Oxidative Balance Score (OBS) is a tool for assessing the oxidative stress-related exposures of diet and lifestyle. The study aimed to investigate the association between OBS and low muscle mass. Methods: Overall, 6307 individuals over the age of 18 were assessed using data from the 2011 to 2018 National Health and Nutrition Examination Survey (NHANES). Weighted logistic regression and models were used, together with adjusted models. Results: There was a negative relationship between OBS and low muscle mass (odds ratio [OR]: 0.96, 95% confidence interval [CI]: 0.94 to 0.97, P<0.0001) using the first OBS level as reference. The values (all 95% CI) were 0.745 (0.527 to 1.054) for the second level, 0.650 (0.456 to 0.927) for the third level, and 0.326 (0.206 to 0.514) for the fourth level (P for trend <0.0001). Independent links with low muscle mass were found for diet and lifestyle factors. A restricted cubic spline model indicated a non-linear association between OBS and low muscle mass risk (P for non-linearity< 0.05). In addition, the inflection points of the nonlinear curves for the relationship between OBS and risk of low muscle mass were 20. Conclusion: OBS and low muscle mass were found to be significantly negatively correlated. By modulating oxidative balance, a healthy lifestyle and antioxidant rich diet could be a preventive strategy for low muscle mass.